KAJIAN STRUKTUR CHECK DAM 3 BATANG HULU KURANJI KOTA PADANG STUDY OF CHECK DAM STRUCTURE 3 BATANG HULU KURANJI PADANG CITY - Silta Yulan Nifen; Afif Dzaky Almy (Ensiklopedia of Journal, 2021)
Batang Kuranji is a river located in Kota Padang. The high rainfall and human factors that cause changes in characteristics, especially in the upstream area make the water from the flow of kuranji stems in the rainy season often overflows, and cause flash floods, therefore built Check Dam at the head of the river batang kuranji to prevent the shallowing of the riverbed. Thisresearch aims toreview the structure of the Check Dam 3 building on Batang Kuranji in the city of Padang. This study refers to SNI 2851:2015 with rainfall data for 15 years used from 2005 to 2019, with batu busuk observation station and rice fields obtained from PSDA. Luas DAS is obtained from ArcGIS Applications. Dari hydroligi analysis obtained rainfall plan (R100th) 153,152 m3/dt with Gumbel method, Discharge flood plan for the 100 year anniversary period used Haspers method obtained (Q100th) 165.19 m3/dt. The type of Check Dam that is planned is the type of pelimpah (head work) with a height of Check Dam 8.5 m. Tilt of the body at the upstream 0.6, the distance between the main dam and sub dam 25.2 m, the thickness of the apron floor 1.6 m, with an estimated volume of sediment flow that can be accommodated by 14797.6 m3. The stability of the Check Dam construction was obtained at a value of 3.43 >1.5 and a sliding of 1.53 > 1.5 with a safety coefficient of 1.5, so that the construction of the Check Dam was stable.